Causes of intercultural conflict and its management styles among students in Sunway University / Srikumar K. Ramayan ... [et al.] - Ramayan, Srikumar K.; Abu Bakar, Intan Abida; Sangaran Kutty, Vijaya Sooria; Keren Rosa, Kamdoum (Universiti Teknologi MARA, Perak, 2020)
The purpose of this study is to discover the causes of intercultural conflict and its management styles among Sunway University students. A total of six participants were selected from among different departments at Sunway university. A qualitative method was used to achieve the objectives of this research through in-depth interviews. the causes of intercultural conflict and its management styles were assessed based on intercultural conflict and intercultural conflict management style theory. The participants' feedback was transcribed and analyzed by using the deductive coding method which identified themes such as intercultural conflict, impact on intercultural conflict on relationships as well as intercultural conflict management styles that comprises of five categories, obliging, dominating, avoiding, compromising and integrating style. The results suggest, misunderstanding, as the main cause of intercultural conflict and it impacts people both positively and negatively depending on the situation. While suggesting avoiding style as the most used style of overcoming intercultural conflict among Sunway university students when it comes to gender, race, religion and cultural issues. The research findings will add to existing work on intercultural conflict and its management styles.